Design And Implementation Of Android-Based Personal Money Monitoring Application - Chystia Aji Putra; Ronggo Alit; Yisti Vita Via; Wahyu SJ Saputra (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Managing personal finances is something that must be faced by everyone. Someone must be able to manage his personal finances and household well. This is done in order to be able to balance income and expenses, meet the necessities of life, and not get caught up in financial difficulties. By applying the correct way of financial management, a person is expected to get the maximum benefit from the money he has. Based on the problems that have been mentioned, it is need to build a personal financial monitoring application. The platform used by this software is Android. This software development is expected to be good solution tosupport everyone's daily life. Purpose of making this application is expected to provide convenience in recording personal finances. In addition, this application is expected to provide a recapitulation report which is according to user's needed. Some of these activities include filling in the incoming money data, filling out the outgoing money data, monitoring recaps in accordance with user's wishes, and making financial recap reports within a certain period of time. Advantage of this application is that it can do recapitulation with pdf file format outputs.Keywords: Android, Money Monitoring